Prevention and treatment of pressure ulcers/injuries: The protocol for the second update of the international Clinical Practice Guideline 2019. Issue 2 (May 2019) - Kottner, Jan; Cuddigan, Janet; Carville, Keryln; Balzer, Katrin; Berlowitz, Dan; Law, Susan; Litchford, Mary; Mitchell, Pamela; Moore, Zena; Pittman, Joyce; Sigaudo-Roussel, Dominique; Yee, Chang Yee; et al.
Abstract: Aim: The European Pressure Ulcer Advisory Panel, the Pan Pacific Pressure Injury Alliance, and the National Pressure Ulcer Advisory Panel are updating the 'Prevention and Treatment of Pressure Ulcers: Clinical Practice Guideline' (CPG) in 2019. The aim of this contribution is to summarize and to discuss the guideline development protocol for the 2019 update. Methods: A guideline governance group determines and monitors all steps of the CPG development. An international survey of consumers will be undertaken to establish consumer needs and interests. Systematic evidence searches in relevant electronic databases cover the period from July 2013 through August 2018. Risk of bias of included studies will be assessed by two reviewers using established checklists and an overall strength of evidence assigned to the cumulative body of evidence. Small working groups review the evidence available for each topic, review and/or draft the guideline chapters and recommendations and/or good practice statements. Finally, strength of recommendation grades are assigned. The recommendations are rated based on their importance and their potential to improve individual patient outcomes using an international formal consensus process. Discussion: Major methodological advantages of the current revision are a clear distinction between evidence-based recommendations and good practice statements and strong consumer involvement. Conclusion: The 2019 guideline update builds on the previous 2014 version to ensure consistency and comparability. Methodology changes will improve the guideline quality to increase clarity and to enhance implementation and compliance. The full guideline development protocol can be accessed from the guideline website (http://www.internationalguideline.com/ ). Highlights: The EPUAP, NPUAP and PPPIA are updating the the International Clinical Practice Guideline for the prevention and treatment of pressure injuries. Fifteen Associate Organizations support the guideline development. A distinction will be made between evidence based guideline recommendations and best practice statements. Several measures are planned to engage consumers in the guideline development.